Self-design Project Based Learning: Alternative Learning in Vocational Education - Hamdani, Aam; Suherman, Amay (Journal of Technical Education and Training, 2021)
The purpose of this study was to obtain a self-design project learning-based practical learning model so that it becomes an alternative learning model to improve work skills. The research method used is design based research. Steps taken to obtain data include FGDs with industry practitioners, vocational school teachers from the mechanical engineering expertise program and professional certification bodies, further limited and extensive testing will be conducted on vocational students. The results of this study obtained the composition of integrative material which is a guide to improve student competence. The steps of this integrative material are able to make learning an industrial nuance. The concept of vocational education is expected to produce students who master competencies according to their fields and match the demands of industrial competence. So that the learning used must be effective and efficient to produce graduates who have the competencies required by industry. Learning using a self-designed project learning model requires students to function as industrial workers who work carefully and produce competencies that are in line with the industry.